Kualitas Mikrobiologi Sosis Fermentasi Daging Sapi dan Domba yang Menggunakan Kultur Kering Lactobacillus plantarum 1B1 - I I Arief; R.R. A Maheswari; T Suryati; . Komariah; S Rahayu (Media Peternakan, 2008)
Lactic acid bacteria of Lactobacillus plantarum 1B1 species was isolated from fresh beef and used as dried starter culture fermented sausage (salami). Dried starter culture was stored at 100C for 0 (control), 15, 30 and 45 days to evaluate the starter viability and its effect on microbiological charasteristics of beef and mutton fermented sausages. Initial viability of dried starter culture of L. plantarum was 7.08 x 1012 CFU/g. There was no alteration (P>0.05) in viability (5.33 x 1012 CFU/g) during 15 days storage. The population significantly decreased (P CFU/g. Dried culture L. plantarum could reduce the quantity of Staphylococcus aureus during 15 days storage, but neither for 30 days nor 45 days storage. Average total coliform increased from 0 days to 15 days storage at less than 0,03 CFU/g to 0.93 x 102 CFU/g, but the number of coliform decreased on 30 days storage at less than 0.03 CFU/g and increased on 45 days storage at 1.2 x 103 CFU/g. Both salami had negative number of Salmonella. Key words: salami, dried starter culture, Lactobacillus plantarum 1B1, storage time